mRNA and protein expression of programmed cell death-ligand-1 on canine mammary gland tumour in dogs of Chiang Mai, Thailand - Srisawat, Wanwisa; Koonyosying, Pongpisid; Muenthaisong, Anucha; Sangkakam, Kanokwan; Varinrak, Thanya; Rittipornlertrak, Amarin; Nambooppha, Boondarika; Apinda, Nisachon; Sthitmatee, Nattawooti (International journal of veterinary science and medicine, 2025)
Metastasis-related disease is a major cause of death in canine mammary tumours (CMTs). Immunotherapy has been investigated due to the less successful outcomes of systemic therapy. This study aims to examine the expression of Programmed Cell Death Ligand-1 (PD-L1) in canine mammary tumours in dogs of Chiang Mai, Thailand, and determine the relationship between the level of mRNA expression and clinicopathologic characteristics. A total of 28 CMT samples were collected at the Small Animal Hospital, Chiang Mai University. Quantitative reverse transcriptase-polymerase chain reaction (RT-qPCR) and western blot assays were performed. The results revealed that all CMTs in this study expressed PD-L1 mRNA and PD-L1 protein. The mean relative mRNA expression showed no significant differences between groups categorized by age, tumour size, or histopathological findings. However, the mean relative mRNA expression in tumours with a TNM stage >3 was significantly lower compared to those with TNM stage ≤2. In conclusion, this study investigates the expression of PD-L1 mRNA and PD-L1 protein, particularly in malignant CMTs. The findings strongly support the potential for developing effective immunotherapy methods targeting the PD-1/PD-L1 pathway for advanced CMTs in the future. For further conclusive assessment, future studies should focus on refining immunotherapy strategies for CMT cases expressing PD-L1.